Efektivitas Beberapa Insektisida Aerosol Terhadap Kecoak Blattella germanica (L.) (Dictyoptera; Blattellidae) Strain VCRU-WHO, GFA-JKT DAN PLZ-PDG Dengan Metode Semprot - Weny Bestari; Resti Rahayu; - Dahelmi; Nova Hariani (Jurnal Biologi Universitas Andalas, 2014)
We examined the effectiveness of some insecticide aerosols to German cockroaches. This experiment was conducted at the Laboratory of Animal Physiology Department of Biology, Andalas University from July to October 2013. Animal subjects were three strains of German cockroaches, namely GFA-JKT from Jakarta, PLZ-PDG from Padang and VCRU-WHO from School of Biological Sciences, University Sains Malaysia. Those subjects were treated using spray method of five brands of commercial insecticides found in the market, namely ByWS, HtWS, MtWS, RdWS and VpWS. We analyzed  knockdown and lethal times using probit analysis. The effectiveness were evaluated based on running time to achieve the knockdown and lethal. The results showed that knockdown time (KT90) of ByWS, HtWS, MtWS, RdWS and VpWS were effective for VCRU-WHO and GFA-JKT strains and the only HtWS and RdWS were effective for PLZ-PDG strain. Based on the the lethal time (LT90)  there was no single insecticide effective to kill cockroach.Kata kunci: Blattella germanica, commercial insecticide, Spray Method, Knockdown.